ANALISIS YURIDIS PUTUSAN PEMIDANAN TERHADAP TINDAK PIDANA PENCURIAN DENGAN KEKERASAN YANG MENGAKIBATKAN MATI - Waruwu, Yustinus Yustus (LPPM Universitas Nias Raya, 2025)
The crime of theft with violence is a criminal act of taking or moving goods without the knowledge and permission of the owner which is preceded, accompanied or followed by violence with the intention of achieving the goal committed. One of the crimes of theft with violence which results in death is tried by a panel of judges. Tarakan district court namely Decision Number: 342/Pid.B/2021/PN.Tar). In this decision the judge decided that the defendant was legally and convincingly proven guilty of committing the crime of theft with violence which resulted in death. Sentenced the defendant to prison for 8 (eight) years. The type of research used is normative legal research using the statutory approach, case approach and analytical approach. Data collection was carried out using primary data, secondary data and tertiary data. The data analysis used is descriptive qualitative analysis and conclusions are drawn using a deductive method. Based on the research findings and discussion, it can be concluded that the juridical analysis of the punishment decision for the crime of theft with violence resulting in death (Study Decision Number 342/Pid.B/2021/PN Tar). That Article 365 paragraph (3) of the Criminal Code as imposed on the perpetrator is not appropriate and does not provide a deterrent effect on the perpetrator. As we can see, the consequences of his actions caused huge losses to the victim's family which resulted in the victim's death. The judge should have decided to sentence the defendant to prison for 12 (twelve) years in accordance with the demands of the public prosecutor.